Pemberdayaan Masyarakat melalui Pelatihan Pembuatan Pupuk MOL dan Pemasaran Digital Berbasis E-Commerce - Hidayatullah, Zul; Nuraini; Ariandani, Nunung; Qusyairi, Muhammad (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
This community service program aims to enhance the knowledge and skills of local communities in producing Local Microorganism (MOL) fertilizers and to strengthen economic capacity through digital marketing based on e-commerce platforms. The target participants of this program are farmer groups and small-scale entrepreneurs in the partner area who have been largely dependent on chemical fertilizers and have limited capabilities in marketing their products online. The implementation methods include educational outreach, hands-on training in producing MOL fertilizers using locally sourced organic waste, and mentorship on utilizing e-commerce platforms for product marketing. The activities are conducted in a participatory manner through educational and demonstrative approaches to ensure active involvement of the participants in each stage. The outcomes of the program indicate an increase in community understanding of the benefits of organic fertilizers and their ability to independently produce MOL fertilizers. Additionally, participants were able to create accounts and market their agricultural products through digital media, such as online marketplaces and social platforms. The expected impact of this program includes the development of a more self-reliant community in managing local resources, reducing dependency on chemical fertilizers, and expanding sustainable agricultural product marketing networks. Thus, this program contributes to improving the local economy while simultaneously supporting environmental conservation efforts through the utilization of organic waste